Effect of Medium Conditioned by Cryopreserved Placental Cells on Organotypic Ovarian Culture - Mykhalchuk, Tetyana; Prokopiuk, Volodymyr; Shevchenko, Mariia; Prokopiuk, Olga (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):293